Psychopathology and Continuous Subcutaneous Insulin Infusion in Type 1 Diabetes - Francesco Rotella; Caterina Lamanna; Ilaria Dicembrini; Carlo Faravelli; Caterina Calasso; Edoardo Mannucci (The Scientific World Journal)
Aim. Continuous subcutaneous insulin infusion (CSII) is used as an option in patients with diabetes failing to multiple daily injections (MDI). Psychological factors may play a relevant role in the failure to attain therapeutic goals in patients on MDI. This could lead to an overrepresentation of psychopathology in patients treated with CSII. Methods. A consecutive series of 100 patients with type 1 diabetes was studied, collecting main clinical parameters and assessing psychopathology with the self-reported questionnaire Symptom Checklist 90-revised. Patients on CSII were then compared with those on MDI. Results. Of the 100 enrolled patients, 44 and 56 were on CSII and MDI, respectively. Among men, those on CSII were younger than those on MDI; conversely, no difference in age was observed in women. Women on CSII showed higher scores on most Symptom Checklist 90 subscales than those on MDI, whereas no differences were observed in men. Conclusion. Women with type 1 diabetes treated with CSII display higher levels of psychopathology than those on MDI. This is probably the consequence of the fact that patients selected for CSII are those failing to MDI. Higher levels of psychopathology could represent a limit for the attainment and maintenance of therapeutic goals with CSII.